Limits of Scientific Thinking (Study of Improving Memorization through Tahfizh Qur'an Program at MTSN 02 Kotawaringin Barat) - Jumiati, Jumiati; Muslimah, Muslimah (CV. Creative Tugu Pena, 2024)
This research aims to analyze the limits of scientific thinking on how to improve memorization of the Al-Quran through the tahfiz program implemented at MTsN 02 Kotawaringin Barat. The research uses a qualitative research approach, a type of field research. Data was extracted through observation, interviews and documents. The subjects of this research were Tahfidz teachers and madrasa heads, while the informants were students, deputy madrasa heads and parents. Data analysis was carried out inductively. The results of this research show that humans were created by God and are perfect and great compared to other living creatures. Humans have minds and hearts. By thinking, a person can think deeply so that he can solve all problems and problems in life, humans will be able to know what is right and wrong, what is good and what is bad, and humans will be able to decide everything, driven by action and performance and needs. The challenging and challenging life problems faced by society over time require humans to think maturely, carefully, quickly and clearly, and have a positive impact on their lives. If thinking ability is low and thinking is slow, people are isolated from life. The Quran is a way of life for Muslims, all Muslims must study and understand it to better teach and develop all aspects of human behavior, so studying the Quran and Sunnah must be used from childhood. Young people can form the basis of mental health. One effort to maintain the purity of the Qur'an is by reading the Qur'an. There are many hadiths of the Prophet SAW that show the greatness of people who read the Koran. Reading the Koran is a noble and praiseworthy act in the sight of Allah, and Allah will place them in heaven with the Prophets. Keywords: Scientific Thinking, Improved Memorization, Al-Qur'an Tahfiz